Distinct Immune Response at 1 Year Post-COVID-19 According to Disease Severity - Kang, Chang Kyung; Kim, Minji; Hong, Jisu; Kim, Gwanghun; Lee, Soojin; Chang, Euijin; Choe, Pyoeng Gyun; Kim, Nam Joong; Kim, Ik Soo; Seo, Jun-Young; Song, Daesub; Lee, Dong-Sup; et al. (Frontiers in Immunology, 2022)
Background. Despite the fact of ongoing worldwide vaccination programs for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), understanding longevity, breadth, and type of immune response to coronavirus disease-19 (COVID-19) is still important to optimize the vaccination strategy and estimate the risk of reinfection. Therefore, we performed thorough immunological assessments 1 year post-COVID-19 with different severity. Methods. We analyzed peripheral blood mononuclear cells and plasma samples at 1 year post-COVID-19 in patients who experienced asymptomatic, mild, and severe illness to assess titers of various isotypes of antibodies (Abs) against SARS-CoV-2 antigens, phagocytic capability, and memory B- and T-cell responses. Findings. A total of 24 patients (7, 9, and 8 asymptomatic, mild, and severe patients, respectively) and eight healthy volunteers were included in this study. We firstly showed that disease severity is correlated with parameters of immune responses at 1 year post-COVID-19 that play an important role in protecting against reinfection with SARS-CoV-2, including the phagocytic capacity of Abs and memory B-cell responses. Interpretation. Various immune responses at 1 year post-COVID-19, particularly the phagocytic capacity and memory B-cell responses, were dependent on the severity of the prior COVID-19. Our data could provide a clue for a tailored vaccination strategy after natural infection according to the severity of COVID-19.